Linking rivers in the Ganges-Brahmaputra River Basin: exploring the transboundary effects - Bhaduri, Anik; Barbier, Bruno (2008)
The following paper explores the possible inter-linkage of the Ganges and Brahmaputra River Basin and analyzes its effect on future water allocation between the upstream country, India, and the downstream country, Bangladesh. We find that water transfer from the Brahmaputra River could be mutually beneficial for both countries. However, the only possible motivation for the richer upstream country, India, to agree to transfer water to the poorer downstream country, Bangladesh, is political altruism. Using a political economy model we find that, if there is a good political relationship between India and Bangladesh, then India could be altruistic toward Bangladesh and transfer more water downstream. Changes in political altruism factor, however, could entice India to exercise unilateral diversion, in which case simulations predict that Bangladesh would incur large environmental damages. Political uncertainty may also result in unilateral diversion of water by India, and could prevent agreement on water transfers from the Brahmaputra. We therefore explore the conditions under which Bangladesh could accept an Indian proposal to transfer water from Brahmaputra, despite political uncertainty.